Does pull-up grip performance influence sprint times in high school female swimmers? - Kruse, J.; Shim, A.; Morgan, V.; Ryan, K. (Journal of Swimming Research, 2020)
Pull-ups have been used as a predictor of swim speeds on young male swimmers but there is a lack of information regarding female swimmers. Therefore, the aim of this study was to determine if a relationship exists between specific pull up grips and 50-meter sprint times in high school female swimmers. A 3 group pre and post four-week design was selected for this investigation. 17 healthy high school female swimmers (age 15.7+ 1.6 years; height 64.94 + 2.6 cm; weight 60.23 + 5.90 kg) from a Midwest high school swim team volunteered to participate. Pre and post-test of pull ups in a neutral grip to fatigue as well as a 50-freestyle for time were performed at maximal effort for all 3 groups. The 2 experimental groups performed a four-week intervention consisting of 3 sets of pull-ups (pronated or supinated grip group), twice a week. The 2 experimental groups used an assistance band at a moderate resistance (Power Systems, Knoxville, TN) to help with completion of pull-ups during the 4 weeks. A repeated measure ANOVA on SPSS (version 26) determined no significance between the 3 groups with sprint times. However, the supinated grip group had significant improvements with pull-ups after the 4-week intervention (p = .022) when compared the other groups. A Pearson correlation of post pull-up scores and post swim times demonstrated a moderate relationship (r=-.563; p= .019), among all 3 groups.